2020
DOI: 10.1002/aoc.5458
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic and hepatoprotective synergistic effects of selenium nanoparticles and vitamin. E against acrylamide‐induced hepatic alterations in male albino mice

Abstract: The potential benefit of selenium nanoparticles (SeNPs) and vitamin E (Vit.E) that they are potent antioxidants , they were used as antioxidants against acrylamide (ACR) hepatotoxicity, ACR is found in the starchy foods that had been heated for long periods in high degrees above 120°C. So the aim of the current study was to elucidate the antihyperlipidemic and hepatoprotective effects of either SeNPs and/or Vit.E against ACR toxicity, SeNPs were characterized by SEM, EDX, TEM and they proved their spherical na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 54 publications
4
22
0
Order By: Relevance
“…(Guo et al 2020), Reham Z. (Hamza et al 2020) and (Al-Quraishy, Adkhil, and Moneim 2015), mentioned, selenium nanoparticles reduce levels of triglycerides, cholesterol and low density lipoprotein, while increasing levels of high density lipoproteins. Which may explain the high levels of vitamin D after adding these particles to the serum, given the possibility of release of vitamin D from the fatty tissue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Guo et al 2020), Reham Z. (Hamza et al 2020) and (Al-Quraishy, Adkhil, and Moneim 2015), mentioned, selenium nanoparticles reduce levels of triglycerides, cholesterol and low density lipoprotein, while increasing levels of high density lipoproteins. Which may explain the high levels of vitamin D after adding these particles to the serum, given the possibility of release of vitamin D from the fatty tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Among the possible causes of vitamin D deficiency in a large proportion of the population, especially those who are overweight or obese, is the fact that the fat tissue has blocked vitamin D within it (McKay et al 2020;Pourshahidi 2015). As Leilei Guo et al (Guo et al 2020), Reham Z. Hamza et al (Hamza et al 2020) and Saleh Al-Quraishy et al (Al-Quraishy, Adkhil, and Moneim 2015), mentioned, selenium nanoparticles reduce levels of triglycerides, cholesterol and low density lipoprotein, while increasing levels of high density lipoproteins. Which may explain the high levels of vitamin D after adding these particles to the serum, given the possibility of release of vitamin D from the fatty tissue.…”
Section: Effect Of Nanoparticles On Vitamin D Levels In Patient Groupsmentioning
confidence: 99%
“…The mechanism involves the regulation of AKT/PI3K and MAPK signaling pathways by gold NPs, thereby reducing pro-inflammatory cytokine secretion and oxidative stress. Another study reported that vitamin E-modified selenium NPs can attenuate liver fibrosis by reducing oxidative stress [ 68 ].…”
Section: Nanomedicine For Liver Fibrosis Therapymentioning
confidence: 99%
“…For many diseases, minerals are also used as inorganic medicines. However, the focus in this article is on of metal molecule interactions, as well as the chemistry and structure of metal complexes [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Current developments in the design of metal-based therapeutic agents have demonstrated increasingly important research attempts to develop new compounds with fewer toxic side effects [4][5][6][7][8]. The present article aimed to study the chemical structures of STG complexes with Mg 2+ , Ca 2+ , Cr 3+ , Zn 2+ , Cu 2+ , and Se 4+ using CHN elemental, molar conductance, FT-IR, magnetic susceptibility, electronic UV-Vis, 1 H NMR, thermogravimetric analysis (TGA/DrTGA), XRD, SEM, and TEM analyses.…”
Section: Introductionmentioning
confidence: 99%